2018
DOI: 10.1021/acs.cgd.8b00091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Conformation on Interactions and Packing in the Crystal Lattice

Abstract: The crystal and molecular structures of a series of structurally related analogues of 1,25-dihydroxyvitamin D2 and of the first analogue with all hydroxyl groups protected were established with single crystal X-ray structural analysis. With the use of the new structural data, we proposed that the A-ring conformation depends on hydrogen bonding of the hydroxyl groups of the A-ring. The A-ring of the 1α-hydroxylated vitamin D analogues exists in the solid state in a preferred chair β-conformation induced by dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…The appearance of particular H-bonded motifs (spiral chains, bilayers, and others) is characteristic for spontaneous resolution of racemic and nonracemic mixtures of some chiral compounds [60][61][62] at crystallizations. Other applications of the analysis of H-bonded associates include salt formation via evaluating synthon competition [63,64], assessing putative structures from crystal structure prediction [65], and analysis of H-bonding in drugs and vitamins [66].…”
Section: Search On Hydrogen-bond Motifsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of particular H-bonded motifs (spiral chains, bilayers, and others) is characteristic for spontaneous resolution of racemic and nonracemic mixtures of some chiral compounds [60][61][62] at crystallizations. Other applications of the analysis of H-bonded associates include salt formation via evaluating synthon competition [63,64], assessing putative structures from crystal structure prediction [65], and analysis of H-bonding in drugs and vitamins [66].…”
Section: Search On Hydrogen-bond Motifsmentioning
confidence: 99%
“…Dehydration and desolvation of lenalidomide follow "isostructurality" in crystal packing: All solvates at heating convert to its' thermodynamically stable anhydrous form, whereas all hydrates upon dehydration convert to a metastable anhydrous polymorph able to transform upon further heating to the stable polymorph [114]. Analysis of H-bonding and crystal packing similarity for the crystal structures of vitamin D analogs showed that various conformations of its A-ring are predetermined by H-bonding of hydroxyl group both in crystals and in the binding pocket of the vitamin D receptor and that the exocyclic methylene group also influences H-bonding pattern in solids [66].…”
Section: Crystal Packing Similarity Toolmentioning
confidence: 99%
“…These patterns are strongly related to the position of the exocyclic methylene group, as this group stabilizes hydrophobic interactions with a triene system only in the natural position, that is, attached to the C10 carbon atom. We showed that infinite hydrogen bond chains are essential in the interactions of vitamin D analogues and lead to a chair β-conformation that has lower energy than the αconformation, and thus enables strong interactions with the VDR [16].…”
Section: Introductionmentioning
confidence: 98%
“…However, the simple structural fragments having their X-ray structures solved might be a valuable source of data in predicting the solid-state structure of the final vitamin D analogues. Despite broad applications and interests in the chemistry of vitamin D, less than 20 crystal structures of active metabolites and various analogues of vitamin D have been solved and deposited in the Cambridge Structural Database (CSD) [15][16][17][18], while ca. 20, 20, and 40 structures of widely used other pharmaceutical compounds were deposited, that is, ibuprofen, acetylsalicylic acid, and acetaminophen, respectively [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation